2015
DOI: 10.1007/s00586-014-3688-x
|View full text |Cite
|
Sign up to set email alerts
|

Do postoperative radiographically verified technical success, improved cosmesis, and trunk shift corroborate with patient-reported outcomes in Lenke 1C adolescent idiopathic scoliosis?

Abstract: Significant, but less than "perfect" correlations were observed between the radiographic, cosmetic measures and patient-rated outcomes. Thoracic AV-CSVL, AV-T1 correction and POTSI associated significantly with SRS-30 scores. Whereas, thoracic Cobb angle, Cobb correction, and coronal balance did not correlate with any patient-rated outcome measure. It is, therefore, inferred that the patients-rated subjective outcomes are only poorly reflected by the objectively measured radiographic and cosmetic measures of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The impact of this new arm position on 3D parameters of the spine and pelvis, spino-pelvic alignment, and postural balance in AIS has not been evaluated. Considering the importance of the 3D spino-pelvic alignment in the characterization of an AIS curve both pre-and post-operatively [23], we aimed to identify the impact of the patients' arm position on the 2D/ 3D spinal parameters and postural balance of AIS. We further sought to determine the arm position that replicates the natural functional balance in AIS which is compatible with simultaneous PA and lateral spinal stereoradiography.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of this new arm position on 3D parameters of the spine and pelvis, spino-pelvic alignment, and postural balance in AIS has not been evaluated. Considering the importance of the 3D spino-pelvic alignment in the characterization of an AIS curve both pre-and post-operatively [23], we aimed to identify the impact of the patients' arm position on the 2D/ 3D spinal parameters and postural balance of AIS. We further sought to determine the arm position that replicates the natural functional balance in AIS which is compatible with simultaneous PA and lateral spinal stereoradiography.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on hybrid constructs found a significant negative correlation between implant density and curve correction [ 37 , 43 , 44 ]. Though, it has been reported that the amount of correction and implant density does not correlate with HRQoL [ 9 , [45] , [46] , [47] , [48] , [49] , [50] ]. Surgical intervention, regardless of the amount of correction, does affect the HRQoL [ 9 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of distal disc degeneration and curve progression is a classic challenge in AIS surgery. However, there is some evidence that a well-balanced lumbar curve is protected from further degeneration following surgery [11].…”
Section: Discussionmentioning
confidence: 99%